Synthesis and Photoluminescence characterization of NaMgSO4F: Ce phosphor - Choube, S R; Gedam, S C; Dhoble, S J (Recent Research in Science and Technology, 2012)
Ce3+ emission in NaMg(SO4)F phosphor prepared by wet chemical method is reported in this paper. The synthesized phosphor is characterized by X-ray diffraction, photoluminescence excitation and emission spectra. The emission spectra shows a dominant peak at 349 nm due to the 5d→4f transition of Ce3 + when monitored at excitation wavelength of 263 nm. In this host very low concentration of cerium is used. The characteristic emission of the NaMg(SO4)F phosphor in the UV region of spectrum makes it a strong candidate for the use in scintillation applications.